Phenolic profile from the pomace of two portuguese grape varieties: sustainability and food safety as new natural additives - Ferreira da Vinha, Ana (2022)
Grapes are one of the most produced fruit crops worldwide. About 75% of produced grapes is planned for wine production, originating 20-30% waste products. This waste is mainly constituted by grape pomace which includes fruit peels, remaining pulp, seeds, and stalks. Moreover, as it is common knowledge that therapeutic properties of plants and their by-products have been increasingly described, because of their strong antioxidant values, absence of side effects, and economic viability. Synthetic antioxidants have been used as supplement added, however, their inclusion in chronic infections have confined their utilization in foods. Grape pomaces have biotechnological potential, having been applied in several studies as a fortification ingredient in foods. Reuse of the grape pomace depends on its composition and characteristics. Because grape pomace is a highly perishable product (due to the high moisture content) and given the high volumes generated during harvest season, the utilization of fresh grape pomace is unfeasible and requires an appropriate method of preservation or appropriate use. Thus, grape pomace can be reused through oil extraction, antioxidant, and antibacterial agents’ preparation and, from a nutritional perspective, polyphenols are the most important constituents. Large amounts of the residual quantities of bioactive substances remain in the vegetable tissues: phenolic acids, several flavonoids, flavanols (e.g., catechin, epicatechin and epigallocatechin) and other phenolic compounds (proanthocyanidins or condensed tannins). Considering the importance of winemaking in Portugal, the phenolic profile of two national grape pomace varieties (Touriga Nacional (red) e Alvarinho (white)) was studied, considering that the extraction of polyphenols from grape pomace represents an attractive, sustainable, and cost-effective source of high-value biological properties, which could be incorporated into foods, as natural additives. Due to the increasing demand for nutraceutical and antioxidant compounds, the study of grape pomace polyphenols exploitation may be useful for industrial purposes. Phenolic compounds were identified and quantified by Reverse-Phase High Performance Liquid Chromatography (RP HPLC) equipped with a diode array detector (HPLC-DAD).